Net water flux and land use shifts across the Brazilian Cerrado between 2000 and 2019 - Silva, César de Oliveira Ferreira; Manzione, Rodrigo Lilla [UNESP]; Caldas, Marcellus Marques (My University, 2023)
Abstract: Water surplus and deficits are crucial concerns in water management with climate change and increasing demand. We investigated spatial and temporal variations in the net water flux (precipitation minus evapotranspiration) as an indicator of water availability over the main water basins of the Brazilian Cerrado biome from 2000 to 2019 (20 years). Net water flux has decreased in all basins during the analyzed period. Through several examples, we hypothesize that land use and land cover changes can provide insights into net water flux dynamics. We found a general trend of increasing evapotranspiration (14.91 mm year - 1) together with decreasing precipitation (- 15.41 mm year - 1) over the entire Cerrado. Results indicated that soybeans and sugarcane crops expansion across the Cerrado biome drove an impact on increasing the evapotranspiration in a scenario of decreasing precipitation, resulting in lower net water flux. A decreasing trend of net water flux was significant in the 5-year periods across all Cerrado biome basins. The nexus between net water flux and land use and cover changes is provided by evidence of evapotranspiration increasing by converting pasture and forest into crops (mostly soybeans). Graphic abstract: [Figure not available: see fulltext.]
Keywords: Hydrology; MOD11A1; MOD16A2; Remote sensing; TRMM